Jogos teatrais, arte na educação: vivências socioeducativas em sala de aula - Fernandez, Claudia Zagatto (2018)
This research has the purpose of studying the theatrical games experienced in classroom. The theatrical games are artistic processes that can become educational by targeting critical and participatory subjects allowing their learning of the school content. We seek to answer the following questions: Can the pedagogy of the experienced question of the theatrical games practice in the classroom contribute to the learners' learning? Do theatrical games allow a better relationship between learners? Does the intervention of the theatrical plays contribute to the teacher's learning? We start up from the idea that the practice of theatrical games in the classroom allows the development of learning, as facilitates a better relationship between learners and qualifies the pedagogical practice as it is the playful complementation belonging to the human being. As a general objective, we seek to analyze whether the pedagogical practice with theatrical games help the learner's learning (living, getting along, knowing oneself, knowing the other, relating to oneself and others). As specific objectives, we highlight the following: to verify if the practice of theatrical games allows the students' learning, to analyze if there were and what were the contributions for personal and interpersonal relationship in classroom with the theatrical games and to identify if the practice of such games contributed to the teacher's learning. The study aimed to establish a dialogue about the importance of the practice of the theatrical Ggames in public school concerning the cognitive and affective development of the students, making possible their politicized citizen formation. The theoretical methodology used was the teaching of theater Theatrical Games, of Viola Spolin, Theater of the Oppressed, by Augusto Boal, and Pedagogy of the Oppressed, by Paulo Freire. The study group was a municipal public school located in the eastern part of São Paulo (SP). The subjects of the study are 30 (thirty) students enrolled in the 5th grade of the interdisciplinary cycle. The mapping of the interactions in the classroom from the theatrical games was based on the proposal collaborative research-critical action defended by Michel Thiollent (2011). The research was based on the following authors: Boal (1991, 2002, 2012), Spolin (2001, 2010, 2015), Freire (1987, 2000). The results observed during this research indicated that theatrical experiences have enabled the learners to transform themselves into citizens who are more aware of the changes they can make in their world, to act in society and face their challenges with more confidence in their own abilities.